A Transcultural Experiment: U.S. Latino Studies at UTS - Paul Allatson (PORTAL: Journal of Multidisciplinary International Studies)
In 2001, shortly after I joined as a newly minted academic the Institute for International Studies at the University of Technology Sydney (UTS), the then founder and Director of the program, Professor David Goodman, approached me to canvas the possibility of a Latino USA Major in the Bachelor of Arts in International Studies (BAIS) degree. These are my reflections on this transcultural experiment in international studies at UTS.